Developing business networking opportunities for SMEs through business ecosystem and ICT. (3rd March 2010) - Perrone, Giovanni; Scarpulla, Lorena; Cuccia, Luigi
Globalisation is a new challenge for European small and medium enterprises; indeed, on one hand, it represents a threat, since new emerging companies are entering their domestic market, but on the other hand, it represents the opportunity to enter new emerging and growing markets. In order to win this challenge, European SMEs need to play the networking card; in fact, it is well acknowledged that networking can improve SMEs effectiveness and efficiency which is absolutely necessary to win the globalisation battle. Many public regional institutions are thinking about how to improve the networking capacity of their SMEs through specific programs and investments. This paper reports the results of an ongoing research project aiming at improving the networking capacity of SMEs through an innovative conception of the business ecosystem idea. The paper shows how the innovative networking business ecosystem has been conceived and how it works for pursuing this aim.